The Using of Biclustering Techniques in Inductive Modeling Systems of Biological Processes - Babichev, V.; Osypenko, V.; Tai, M.; Lytvynenko, V. (Індуктивне моделювання складних систем, 2015)
In article studied the possibility using of bicluster analysis in clustering systems of complex biological nature objects. Biclustering was performed by use the algorithm BCCC of package "biclust" of software environment R, clustering of objects in each bicluster was performed by use the algorithm SOTA. The ratio of the average Euclidean distance between objects in different clusters and individual cluster accordingly were used as the criterion for an estimation of quality clustering. Досліджена можливість застосування бікластерного аналізу в системах кластеризації об'єктів складної біологічної природи. Бікластерізація проводилася за алгоритмом ВССС пакету "biclust" програмного середовища R, кластеризація об'єктів в бікластерах проводилася за алгоритмом SOTA. Критерієм оцінки якості кластеризації було відношення середньої евклідової відстані між об'єктами в різних кластерах і в окремих кластерах відповідно. Исследована возможность применения бикластерного анализа в системах кластеризации объектов сложной биологической природы. Бикластеризация проводилась с использованием алгоритма ВССС пакета “biclust” програмной среды R, кластеризация объектов в бикластерах производилась с использованием алгоритма SOTA. В качестве критерия оценки качества кластеризации использовалось отношение среднего евклидового расстояния между объектами в разных кластерах и в отдельных кластерах соответственно.